KEANEKARAGAMAN DAN KELIMPAHAN JENIS BURUNG PADA TAMAN KOTA SEMARANG, JAWA TENGAH - Bimo Ghifari; Mochamad Hadi; Udi Tarwotjo (Departemen Biologi, Fakultas Sains dan Matematika Undip, 2016)
The City Park is conceived as a space that contains the elements of nature and landscape which is caused by vegetation diversity, activity and artificial elements that are provided as a social and recreational facilities, as well as a breathing space in the city. The Semarang State Park is one of the green open area that are also used by birds. On the other hand the city park has a problem that threatens the existence of birds especially the uncontrolled development. The diversity of the species of birds can be used as indicators of environmental quality, because their life is influenced by the physical, chemical, and biological cchanges in the environment. The research objective was to determine the diversity and abundance of the bird species, determine the composition of the guild of bird species, and to determine the status of the scarcity of birds in the city garden of Semarang. The research was conducted in July-August 2016, where observation was carried out in six state parks in Semarang using the point count method. The analysis of the index used are the abundance of species, species diversity index, evenness index, similarity index, chi square test and hucthinson method.Where795 individuals of birds were observed, covering 27 species and 17 families. The diversity of bird species index categorized moderately were 2.19 to 2.33, except on Park Madukoro which had the lowest category. The birds were categorized evenly with the index 0.74-0.83, except in the Madukoro Wildlife where the categories were fairly even. The composition of the most abundant guild is a group of insectivorous which is 41%. There are 27 species of birds in all six State Parks in Semarang which however have the status of Least Concern by the IUCN. Based on Government Regulation No. 7 of 1999, there are four species of birds included into the category which are protected.Keywords: State Parks, bird, diversity, abundance, composition guild